Some study results of Cam Ranh - Binh Thuan mud eruption strip - Thom*, Bui Van; Trinh, Phan Trong; Tu, Ngo Tuan; Duong, Nguyen Anh; Manh, Nguyen Dang (Vietnam Journal of Earth Sciences, 2016)
Most of the mud eruption locations are distributed in a stretching strip, running in NE-SW direction from Cam Ranh - Ninh Thuan - Binh Thuan NE-SW tectonic fault zone and coinciding with a tectonically crushed zone. The erupted mud consists of sand, mud, clay. The clay contains alkaline montmorillonite, formed following chemical weathering and re-sedimentation processes from rocks containing alkaline minerals in a semi-arid climate area, located in a low terrain or a tectonic subsiding zone with a large fluctuation in groundwater level. The mud eruption  has a close relation to factors (of) climate, topography, geomorphology, hydrogeology, petrography and tectonic activities in the area. Among these, tectonic factors are the most important for they create not only soil and rock crushed zone, paving favorable conditions for strong weathering process at depth, but also to form canals to bring hot groundwater and minerals from certain depths upward, and by the effects of pressurized groundwater and partly due to the expansion in volume of bentonite clay pushing the muddy clay material through the tectonic cracks to the surface of the current terrain. The mud eruption process is not deep; but it may occur from a shallow level, about 4-18 m below, under the impact of the above elements.ReferencesCao Dinh Trieu, 2006. Characteristics of Earthquake Activities of Central Southern and Southern Sea.  Journal of Geology, Range A, 293(3-4), Hanoi.   Cao Dinh Trieu, et al., 2013. Modern geodynamics in Vietnamese territory. Natural Sciences and Technology Publishing House, Hanoi, 242.Ho Vuong Binh, et al., 1990. Research report on evaluation of prospects and possibility of using alkaline bentonite at Thuan Hai. Archived at the Center for Information & Archives of Geology, Hanoi.Le Duc An, 1990. Geomorphological and neotectonic features of Thuan Hai area. Geological Science and Technique Information, (1-2), 5-25, Hanoi.Le Duy Bach, et al., 2007. Tectonic features Pliocene - Quaternary at Southeast continental shelf of Vietnam. Journal of Sciences of the Earth, 29(3), 218-227, Hanoi.Mazzini. A, A. Nermoen, M. Krotkiewski, Y. Podladchikov, S. Planke, H. Svensen, 2009. Strike-slip faulting as a trigger mechanism for overpressure release through piercement structures. Implications for the Lusi mud eruption, Indonesia. Marine and Petroleum Geology, doi:10.1016/j.marpetgeo.2009.03.001Medialdea. T, et al., 2003. Tectonics and mud eruption  development in the Gulf of Cadiz.  Marine Geology, 261(1-4), 48-63.Nguyen Duc Thai, et al., 2011. Report on survey results of land crack and mud appearance locations at Suoi Da village, Loi Hai commune, Thuan Bac district, Ninh Thuan province. Archived at Division for Water Resources Planning and Investigation for the Central Region of Vietnam.Nguyen Duc Thang (chief author) et al., 1988. Report on surveying and mapping of Geology and Minerals in Phan Rang-Nha Trang area at 1:200,000 scale. Archived at the Center for Information & Archives of Geology, Hanoi.Nguyen Hong Phuong, 2004. Map of earthquake dangerous rate in Vietnam and the East Sea. Journal of Sciences of the Earth,  26(2), 97-111, Hanoi.Pham Van An, et al., 1990. Features of weathering crust at dry hot area Thuan Hai and origin of alkaline bentonite clay. Geological Science and Technique Information, (1-2), 72-79, Hanoi.Pham Van Hung, 2000. Determining kinematic properties of cracks by analyzing tectonic cracks in the South Central region, Journal of Sciences of the Earth, 29(2), 113-119, (in Vietnamese).Pham Van Hung, 2001. Quaternary - modern operational features of tectonic fault at the East edge of Kon Tum massif. Journal of Geology, 267, 43-49, Hanoi.Pham Van Nam, et al., 1988. Report on hydrogeological-engineering geological Mapping at 1:200,000 scale in Phan Rang-Nha Trang region. Archived at Division for Water Resources Planning and Investigation for the Central Region of Vietnam, Nha Trang.Phan Trong Trinh, 2012. Recent tectonics and modern geodynamics in Vietnam’s Sea and adjacent zones. Natural Sciences and Technology Publishing House, Hanoi, 331p.Pham Van Thuc, et al., 2004. Seismic zoning of the East Sea and coastal area in Vietnam. Journal of Geology, Range A, 285(11-12), Hanoi.Phung Van Phach, et al., 1996. Some research results of gases ash eruption phenomenon at Pleiku Highland in 1993. Geological Resources, 1, Science and Technique Publishing House, 396-405.Quo-Cheng Sung, Hung-Cheng Chang, HSing-Chang Liu, Yen-Chieh Chen, 2010. Mud eruption along the chihan fault in Southwestern Taiwan Arelease bend model. Geomorphology, 118, 188-198.Tran Van Thang, et al., 2006. Tectonic development characteristics of Da Lat zone and adjacent zone in late Mezozoi-Kainozoi. Journal of Sciences of the Earth, 28(2), 140-149, (in Vietnamese)..Stepanek P., Ho Trong Ty, 1986. Report on mineral geological mapping at Phan Rang-Cam Ranh at 1:50,000 scale. Archived at the Center for Information & Archives of Geology, Hanoi.Vo Cong Nghiep, et al., 1998. List of hot water and minerals resources in Vietnam. Ministry of Industry, General Department of Geology and Minerals of Vietnam, Hanoi. 308p.Uong Dinh Khanh, 2004. Geomorphological characteristics of the hilly areas Ninh Thuan - Binh Thuan. Doctorate thesis, archived at National Library, Hanoi.Yin. P, S. Bern, P. Vagner, B. Loubrieu, Z. Liu, 2003. Mud eruption at the shelf margin of the East China Sea. Marine Geology, 194(3-4), 135-149.http://www.mhc.vn/. Minh Ha Bentonite Minerals JSC.